2021
DOI: 10.1111/1365-2656.13623
|View full text |Cite
|
Sign up to set email alerts
|

Climate differently influences the genomic patterns of two sympatric marine fish species

Abstract: Climate influences population genetic variation in marine species. Capturing these impacts remains challenging for marine fishes which disperse over large geographical scales spanning steep environmental gradients. It requires the extensive spatial sampling of individuals or populations, representative of seascape heterogeneity, combined with a set of highly informative molecular markers capable of revealing climatic‐associated genetic variations. We explored how space, dispersal and environment shape the geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 157 publications
0
13
0
Order By: Relevance
“…Going forward, we expect to see an increase in the use of genomic markers, as these not only have much greater power to detect genetic structure by means of selectively neutral markers but can also be used to identify gene-environment interactions and highlight intraspecific adaptive signals (Helyar et al, 2011). As neutral and adaptive genetic patterns have been shown to differ (Boulanger et al, 2021;Liggins et al, 2020;Milano et al, 2014;Torrado et al, 2020), comparing adaptive signals across multiple taxa would provide an interesting addition to the present study, and could allow identifying environmental and climatic features causing local adaptation of marine species. For example, showed that genomic vulnerability under climatic change differs between sympatric species requiring alternative solutions for protecting intraspecific diversity.…”
Section: The Future Of Molecular Research On Southern Africa's Marine...mentioning
confidence: 99%
“…Going forward, we expect to see an increase in the use of genomic markers, as these not only have much greater power to detect genetic structure by means of selectively neutral markers but can also be used to identify gene-environment interactions and highlight intraspecific adaptive signals (Helyar et al, 2011). As neutral and adaptive genetic patterns have been shown to differ (Boulanger et al, 2021;Liggins et al, 2020;Milano et al, 2014;Torrado et al, 2020), comparing adaptive signals across multiple taxa would provide an interesting addition to the present study, and could allow identifying environmental and climatic features causing local adaptation of marine species. For example, showed that genomic vulnerability under climatic change differs between sympatric species requiring alternative solutions for protecting intraspecific diversity.…”
Section: The Future Of Molecular Research On Southern Africa's Marine...mentioning
confidence: 99%
“…A single locus was found to have a highly significant role in shaping the sea age at maturation in this species. A survey of a few thousand SNPs in Mediterranean populations of sea bream Diplodus sargus and striped red mullet Mullus surmuletus revealed outlier SNPs correlated with temperature in the latter only [ 210 ]. The blue shark Prionace glauca was thought to have a panmictic world-wide population.…”
Section: Selection and Adaptation Of Aquatic Populations To Environme...mentioning
confidence: 99%
“…To capture such exceptional long‐distance dispersal events, we performed an exhaustive sampling design – along a 4000 km coastline – that encompasses the full geographic range of the white seabream D. sargus across the Mediterranean Sea. We genotyped a total of 297 individuals at 8206 single nucleotide polymorphisms (SNPs) (Boulanger et al 2022) to shed light on long‐distance dispersal movements over one generation. We estimated six relatedness coefficients among pairwise individuals, and we used a maximum likelihood method to assign sibship (Method, Supporting information).…”
Section: Figurementioning
confidence: 99%